PENDEKATAN METODE BERCERITA UNTUK MENDUKUNG PERKEMBANGAN BAHASA PADA ANAK SPEECH DELAY - Rahmawati, Heny Kristiana; Rissa Wahyuningtyas (LPPM IAD Probolinggo, 2024)
Basically, every child has the right to grow and develop in their life. The main problem in this study is the language development of speech delay children at the Bureau of Psychology. Speech delay itself is a condition of children who experience delays in speaking. This study aims to describe efforts to develop language using the storytelling method on the speaking ability of children with speech delay at the Jepara Applied Psychology Bureau. This study uses a research method with a descriptive qualitative research type. The data sources for this study are primary data and secondary data. Data collection techniques were obtained through interviews, observations, and documentation at the Jepara Applied Psychology Bureau. The research data sources were obtained from the head of the bureau, counselors or therapists, and parents of speech delay children. The results of the research in the field succeeded in obtaining several findings, namely: Application of the storytelling method as an effort to develop the language of speech delay children. The media used are dolls, surrounding objects, and fairy tale books. The steps used start from praying, mouth exercises, applying the storytelling method, relaxation, re-telling, and closing. In addition, guidance and counseling services are provided by counselors to parents as supporting steps. From the implementation process, several obstacles were obtained such as children having tantrums, falling asleep, being lazy to express themselves, and children being passive. However, the application of the storytelling method has several developments, such as children being able to make sentences, being able to interact with other people, and being able to respond to other people's communication. Keywords: Language development; Speech delay; Storytelling method.